2020
DOI: 10.7341/20201614
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-oriented business process management as a catalyst to the existence of network organizations

Abstract: Nowadays, more and more often, we are dealing with the emergence of network organizations. These are organizations set up to accomplish specific tasks and are created by unrelated organizations. Choosing such a partner cannot be and is not accidental. It is a process in which knowledge about a possible partner and its resources as well as opportunities are used. The author puts forward the thesis that the organization's orientation both on business processes and knowledge management is a strong determinant for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…In this current work, we view the firm's attempts to gain tangible and intangible resources from multiple overlapping standpoints grounded in strategic management. We follow Sobolewska's (2020) view that externally gained knowledge is a complementary resource that is considered as an opportunity, accessed through networking, to supplement the firm's own insufficient resources. In entrepreneurship and strategic management, resource management is a dynamic capability necessary for survival and continuance, particularly under conditions of environmental uncertainty and recognized resource scarcity (Brush et al, 2001;Grichnik, Brinckmann, Singh, & Manigart, 2014).…”
Section: Resource-based View Of the Firm Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In this current work, we view the firm's attempts to gain tangible and intangible resources from multiple overlapping standpoints grounded in strategic management. We follow Sobolewska's (2020) view that externally gained knowledge is a complementary resource that is considered as an opportunity, accessed through networking, to supplement the firm's own insufficient resources. In entrepreneurship and strategic management, resource management is a dynamic capability necessary for survival and continuance, particularly under conditions of environmental uncertainty and recognized resource scarcity (Brush et al, 2001;Grichnik, Brinckmann, Singh, & Manigart, 2014).…”
Section: Resource-based View Of the Firm Perspectivementioning
confidence: 99%
“…In turbulent environments, firms cannot easily foresee which resources will be vitally important; thus it is crucial to invest in network relationships that are believed to increase the number and type of available resources (Johannisson, 1986;Sobolewska, 2020). Social and economic supportive environmental conditions were considered by Bitowska (2020) to be important in overcoming or adapting to uncertainties.…”
Section: Supportive Environmentmentioning
confidence: 99%
“…Literature studies have revealed the so far very meager and scattered work in the field of embedding cooperation between enterprises in interorganizational networks, which definitely does not sufficiently describe the impact of the context of collaboration on enterprise cooperation Sobolewska, 2020). The conducted studies prove that a research area has been identified that has not yet been extensively explored, a fact which requires undertaking work to strengthen the theoretical and empirical approach.…”
Section: Introductionmentioning
confidence: 98%
“…Literature studies have revealed the so far very meager and scattered work in the field of embedding cooperation between enterprises in interorganizational networks, which definitely does not sufficiently describe the impact of the context of collaboration on enterprise cooperation (Lis, 2019;Sobolewska, 2020). The conducted studies prove that a research area has been identified that has not yet been extensively explored, a fact which requires undertaking work to strengthen the theoretical and empirical approach.…”
Section: Introductionmentioning
confidence: 99%